2014
DOI: 10.2152/jmi.61.126
|View full text |Cite
|
Sign up to set email alerts
|

Ctip2-mediated <I>Sp6</I> transcriptional regulation in dental epithelium-derived cells

Abstract: Tooth development relies on the interaction between the oral ectoderm and underlying mesenchyme, and is regulated by a complex genetic cascade. This transcriptional cascade is regulated by the spatiotemporal activation and deactivation of transcription factors. The specificity proteins 6 (Sp6) and chicken ovalbumin upstream promoter transcription factor-interacting protein 2 (Ctip2) were identified in loss-of-function studies as key transcription factors required for tooth development. Ctip2 binds to the Sp6 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…We also found that BMP2 could positively support amelogenesis in vitro (Miyoshi et al , ) and that SP6 could downregulate follistatin ( Fst ), a BMP antagonist (Ruspita et al , ). We further confirmed in vitro that BMP2 and wingless‐type MMTV integration site family member (Wnt) were the positive regulators of Sp6 expression (Wahyudi et al , ), while chicken ovalbumin upstream promoter transcription factor‐interacting protein 2 (Ctip2) was a negative regulator (Adiningrat et al , ). Furthermore, we found that rho‐associated protein kinase 1 (ROCK1) was positively regulated by SP6 in dental epithelium‐derived cells (Yanuaryska et al , ).…”
Section: Introductionmentioning
confidence: 55%
“…We also found that BMP2 could positively support amelogenesis in vitro (Miyoshi et al , ) and that SP6 could downregulate follistatin ( Fst ), a BMP antagonist (Ruspita et al , ). We further confirmed in vitro that BMP2 and wingless‐type MMTV integration site family member (Wnt) were the positive regulators of Sp6 expression (Wahyudi et al , ), while chicken ovalbumin upstream promoter transcription factor‐interacting protein 2 (Ctip2) was a negative regulator (Adiningrat et al , ). Furthermore, we found that rho‐associated protein kinase 1 (ROCK1) was positively regulated by SP6 in dental epithelium‐derived cells (Yanuaryska et al , ).…”
Section: Introductionmentioning
confidence: 55%
“…Additionally, these mice exhibit dental and periodontal defects as well as altered amelogenesis (Aïoub et al, 2007;Babajko et al, 2015;Nakatomi et al, 2018). An important transcription factor in amelogenesis, Sp6, is also a direct transcriptional target of Bcl11b (Adiningrat et al, 2014;Smith et al, 2020). Homozygous mice (Sp6-/-) have severe defects in teeth, as well as defects in skin, hair follicles, and digit formation (Nakamura et al, 2008).…”
Section: Influence Of Bcl11b In Tooth Formation and Growthmentioning
confidence: 99%